Employee Performance Analysis at Buffet Tuah Bintan Restaurant (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
This research aims to analyze employee performance and service quality at the Tuah Bintan Buffet Restaurant. The research approach used is qualitative with interviews and observation methods as the main data sources. The research results show that optimal employee performance, including clear division of tasks, structured training and regular evaluations, contributes significantly to the quality of services provided. The main challenge faced by this restaurant is maintaining consistent food quality and efficient service times during peak hours. However, innovation and implementation of improvements based on customer feedback have succeeded in increasing customer satisfaction. This research confirms that good employee performance has an important role in creating a positive service experience, as well as providing input for strategies for improving restaurant operations in the future.